Hubungan Tingkat Pengetahuan dan Sikap Masyarakat dalam Mengelola Sampah Berbasis Bank Sampah di Kabupaten Bantul - Bambang Suwerda; Sudibiyakto Sudibiyakto; Andri Kurniawan (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
The increasing amount of waste generation has caused many serious and complex problems inmany areas. Meanwhile, the existing waste management conducted by the community, i.e. ‘collect-carry-throw’ system can cause environmental problems. Therefore, it is necessary to look forother alternatives that are more environmentally friendly, one of which is by waste bank system.However, community participation in Bantul Regency in sorting and saving their waste in wastebanks is still low. It can be seen that only 10.28 % who sort and partially utilize their waste,whereas 13.41 % sort and discard, and 76.31 % do not sort at all. The reason why they do notsort the waste, respectively from the highest percentage is because of: lazy (40.56 %), do notknow that garbage must be sorted before disposed (33.33 %), do not have the facilities (11.79%), unprofitable (10.48 %), and there is no regulation (3.92 %). The purpose of this study was toknow the relationship between knowledge and attitude of the society in waste managementbased on Waste Bank system in Bantul Regency. The study was an observational analytic research with purposive sampling. From the selected 127 respondents, the result of statistical analysis by using Spearman correlation test, obtained p-value < 0.001, and a correlation coeffcientof 0.433. So, it can be concluded that there is a significant correlation between knowledge leveland attitude of community in in terms of waste managemen through Waste Bank approach, andthe correlation has medium strength.